Urgency of Halal Certification for Chicken Slaughterhouses Under Law Number 33 of 2014 and MUI Fatwa - Nihayah Mutmainnah; Muhammad Alwi Sihab Bashari (Commodities, Journal of Economic and Business, 2026)
This study aims to analyzing the urgency of halal certification in the chicken slaughtering process at the poultry slaughterhouse according to Law No. 33 of 2014 and MUI Fatwa No. 12 of 2009. This research is a type of empirical juridical research that uses a sociological approach to law and legislation. The data collection techniques used were observation, interviews, and documentation. The data sources used are primary data sources, which include interviews with chicken slaughterhouse owners, chicken slaughterers, and the surrounding community. Meanwhile, secondary data includes Law No. 33 of 2014 concerning halal product guarantees, MUI Fatwa No. 12 of 2009 concerning halal slaughtering standards, and scientific literature. In Jember Regency, there are 15-20 chicken slaughterhouses, and only one RPA has been certified as halal. The results obtained from this study indicate that the chicken slaughtering process at several RPAs in Jember Regency has been carried out in accordance with Islamic law as stipulated in MUI Fatwa Number 12 of 2009 concerning Halal Slaughtering Standards. However, several of these RPA do not yet have halal certification as required by Law No. 33 of 2014 concerning Halal Product Guarantee. This is due to the low level of understanding among business actors regarding the legal obligation of halal certification and the assumption that halal status is sufficiently determined by the conformity of the slaughtering process with Islamic law. Therefore, efforts are needed to increase awareness, provide assistance, and conduct supervision by the government and relevant institutions so that RPA business actors better understand the importance of halal certification and are encouraged to immediately undergo the halal certification process.